Facing torture through art and the afterlives of war: behind the mask - Mills, Laura (Contesting torture, 2023)
The nexus between art and torture has a long history, yet the discipline of International Relations has largely failed to engage with this potent affective/aesthetic site and the critical opening up of unseen possibilities around “knowing” torture that such engagements engender. In response, this chapter considers US veteran artist, Eli Wright, a former combat medic in Iraq, and his artwork, Torture Mask Triptych, in attempts to open up these possibilities. In its exploration of torture via a narrative approach, this chapter embraces a scholarship of discomfort to unveil multiple contestations, in terms of the sites and subjects under examination and the modes of (un)knowing it pursues. To view torture as/from a site of discomfort reveals troubling slippages in understandings of/around (the) tortured, torturer, and torturing that in turn lead to more subversive and destabilising critical insights around torture and its contestation in the War on Terror.